Politics and documentary culture: the bishops of North-Western Italy during the post-Carolingian period (c. 888-962) - Baitieri, Michele (2020)
This thesis undertakes an extensive study of the early medieval documentation extant for northern Italy in order to show how the period c. 888-962 represented a turning point for the engagement of bishops of the region with politics, both at a high and local level. Scholarship on the Kingdom of Italy has often neglected the post-Carolingian period and misrepresented this phase as a time of chaos after the collapse of the Carolingian Empire or a mere prelude to the central Middle Ages when the Italian communes were born. Only in the last few decades the history of the post-Carolingian Kingdom of Italy has been addressed as a period in its own right. These studies have argued that the period c. 888-962 did not represent a turning point in the history of the Peninsula, but it was rather characterised by a gradual transformation of social relations. Structures of power, behaviour of the élites and economic organization, all show a strong continuity with the Carolingian period, whilst the subsequent localization of power (during the twelfth century) was not caused by the collapse of the Carolingian Empire; it was instead its ‘natural’ evolution in the long term. However, the present study shows how by focusing on the documentation extant for the period, and especially on its graphic features it is possible to appreciate how that same period actually represented a turning point in the engagement of bishops of the region with politics. Milan, Novara, Bergamo and Vercelli have been chosen as four case studies owing to the relatively rich documentary material extant for those dioceses. Part I of the thesis is spilt in four chapters, one for each of the four dioceses selected as case studies, and focuses on episcopal diplomas. Each chapter first provides a detailed overview of the documentation extant for the diocese discussed as well as its archival history, and then tackles the early medieval episcopal diplomas extant for it. While showing how these charters represented a documentary typology in their own right, this section also stresses that graphic and textual features of those same documents enable to grasp both an enhancement of the political engagement of bishops of the region and the emergence of a specific representation of their role during the post-Carolingian period. Moreover, this section demonstrates how graphic features of episcopal diplomas can help to shed new light on further issues, namely the level of graphic education of northern Italian clergy and the debated existence of organised episcopal chanceries. Part II of the thesis is divided in two Chapters, dealing respectively with sovereign diplomas and episcopal charters of exchange. Chapter 5 tackles sovereign diplomas issued in favour of northern Italian episcopal churches. In agreement with recent scholarship, this section does not see these documents as a sign of an alleged onset of episcopal lordship, which supposedly saw bishops asserting their control over the cities of the Kingdom of Italy to the detriment of local representative of the public authority. Nevertheless, it is argued here that the analysis of the graphic features of these documents allows to see how, starting form the last decades of the ninth century, sovereign diplomas were at times actual instruments of episcopal politics, conceived by bishops of the region and written by members of their entourage. Finally, Chapter 6 focuses on the engagement of northern Italian bishops with local politics and the ways in which they represented their role. Textual and especially graphic features of episcopal charters of exchange shows how it was during during the post-Carolingian period that bishops of the region successfully asserted their pivotal role in local politics, at least from a patrimonial point of view. As revealed by the analysis of extant episcopal charters of exchange, during the period c. 888-962 these prelates established a tighter control over the patrimonial administration of the ecclesiastical institutions of their dioceses and the documentation pertaining to it. Overall the thesis demonstrates the importance of graphic features of extant post-Carolingian documentation from northern Italy in order to uncover how that period represented a turning point in the engagement of bishops of the region in both high and local politics. The appreciation of these so far little-studied features enables the present work to stress the existence of an enhancement in the political action of northern Italian bishops in the period c. 888-962. Furthermore, the thesis shows how that enhancement of episcopal engagement in high and local politics also resulted in a shift in the ways in which those prelates represented their role at the time. During the central decades of the tenth century both episcopal diplomas and episcopal charters of exchange reveal that bishops of the region no longer conceived and represented their role as a shared responsibility of bishop and diocesan clergy, but rather as the domain of the bishop alone.